Mass selected clusters on weakly interacting surfaces investigated with UPS - Schröder, Christoph (Technische Universität Dortmund, 2015)
Mass-selected copper clusters, silver clusters, iron clusters and C60 molecules were deposited on thin rare gas layers (xenon, krypton and argon) to investigate the influence of weakly interacting surfaces on the electronic structure of the clusters. Ultraviolet photoelectron spectroscopy (UPS) was used to image the electronic states of the deposited clusters with a photon energy of 11.62 eV. Gas phase cluster spectra from [Häkkinen et al. (2004); Kostko (2007); Cheshnovsky et al. (1990); Taylor et al. (1992)] are compared with the deposited cluster spectra in order to determine the influences of the surface. UP spectra for the resilient C60 molecule were measured to obtain information about the energetic shift between deposited and gas phase clusters. It was found that there is an additional shift of the spectra by the amount of the electron affinity of the supporting rare gas layer. Further investigations with Cu309 clusters showed the same effect, which justifies the application to the cluster spectra. The comparison between the deposited metal clusters with the same cluster size in the gas phase shows evidence of a quantized signal in the s-p-band region of the clusters. The spectra of Cu147 clusters on various substrates agree with the spectra of free Cu147 clusters. In the outlook the preparation and surface characterizing measurements with LEED and STM of Al2O3/Ni3Al(111), as a functionalized cluster support, is presented.
Keywords: Mass selected; Cluster; Copper; Silver; Iron; C60; UPS; Surface; Rare gas; STM; LEED; Nanoparticle; 530; Oberfläche; LEED; Ultraviolett-Photoelektronenspektroskopie; Nanopartikel